Cancer screening educational interventions in rural and farmworker communities: a systematic literature review - Liu, Anni; Garcia-Torres, Laura C.; Johnson, Caitlyn; Haver, Mary Katherine; Gwede, Clement K.; Christy, Shannon M. (Ethnicity & health, 2023)
Men and women living in rural communities of the United States (US) are less likely than those in urban or suburban communities to be up to date with cancer screenings. Delayed screening contributes to later stage at diagnosis and higher cancer mortality for individuals living in rural areas. These effects may be compounded in some rural subpopulations (e.g. migrant and seasonal farmworkers). This systematic review examines educational interventions aimed at increasing colorectal, breast, prostate, oral, and/or cervical cancer screening in the rural US, with special consideration for the farmworker subpopulation. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, our systematic literature review employed the following databases: Ovid MEDLINE, CINAHL Complete, Embase, and Web of Science. Search terms included, but were not limited to 'rural,' 'cancer screening,' 'farmworker,' and 'cancer prevention.' Eligible studies featured an educational intervention implemented in agricultural or rural US settings with a cancer screening behavioral outcome, male and/or female participants, and were published in English between 2002 and 2020. Article screening and data extraction were conducted by two independent reviewers. Twenty-six articles were eligible. Of the six studies focused on the farmworker population (n=2,732), 61.75% of participants reported Hispanic ethnicity. Of the sixteen studies on unspecified rural communities reporting participant race/ethnicity (n=10,442), 39.29% reported Black/African American race. Efficacious interventions included culturally-targeted educational materials, lay health advisors (LHAs), and components that addressed practical barriers (e.g. financial or logistical). Results demonstrate the value of LHAs and targeted education to increase screening for multiple cancer types in rural communities. Prospective research should incorporate and facilitate access to screening and provider-level and/or organizational-level interventions to increase overall impact. HPV: human papillomavirus; LHA: lay health advisors; MeSH: Medical Subject Headings; PRISMA: Preferred Reporting Items for Systematic Reviews and Meta-Analyses; RCT: randomized controlled trial; US: United States